Pharmacokinetic and Pharmacodynamic evaluation of Camptothecin encapsulated Poly (methacylic acid-co-methyl methacrylate) nanoparticles - Mahalingam Manikandan,Krishnamoorthy Kannan (Journal of Applied Pharmaceutical Science, 2017)
Objectives: Camptothecin is an anti-cancer drug widely used for treating colon cancer. Oral delivery of camptothecin is limited by low bioavailability and gastrointestinal toxicity. In order to enhance its potency and improve bioavailability, camptothecin encapsulated Poly (methacylic acid-co-methyl methacrylate) nanoparticles were formulated. The objective of the present investigation is to explore the anti-cancer efficacy and also to define the pharmacokinetics of the prepared camptothecin nanoparticles. Material and method: 1,2 Dimethylhydrazine, Caco-2 cell lines were obtained and used. The pharmacokinetic and pharmacodynamic evaluation of prepared camptothecin nanoformulation was studied in comparison with the pure camptothecin. Results and Conclusion: Camptothecin nanoparticles were comparatively more effective than pure camptothecin against CaCo2 cell line and posses in vivo anti-cancer activity against 1,2 dimethylhydrazine (DMH) induced colon carcinogenesis. The pharmacokinetic study revealed that the prepared camptothecin nanoformulation shows improved bioavailability and had a longer half life than pure camptothecin in rats. Thus, the results demonstrated that the camptothecin nanoformulation may be considered as an oral chemotherapeutic agent for treating colon cancer.
Keywords: Camptothecin,Nanoformulation,Colon cancer,Pharmacokinetics.